2021
DOI: 10.1002/jsfa.11440
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment improves the sensory properties of the ultrafiltration by‐product of honeybush (Cyclopia genistoides) extract

Abstract: BACKGROUND: Ultrafiltration of green honeybush (Cyclopia genistoides) extract results in a by-product (retentate). Application of further separation processes for recovery of polyphenols would entail creation of additional waste. Repurposing the retentate as a food flavour ingredient provides an alternative valorization approach. RESULTS: The retentate, suspended in water (270 g L −1 ), was heat-treated at 80 °C for 2, 4, 8 and 16 h, and at 90 °C for 2, 4, 6 and 8 h to change its sensory profile. The heat-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…This is in accordance with the findings of Lee and Chambers [ 50 ], who found that bitterness and astringency become stronger while green-related attributes become weaker as the brewing time and water temperature of green tea increases. This is also confirmed by the results of Miller et al [ 51 ], who found that heat treatment of 2 h at 80 and 90 °C reduced the green/grass flavors’ intensity to negligible levels.…”
Section: Discussionsupporting
confidence: 87%
“…This is in accordance with the findings of Lee and Chambers [ 50 ], who found that bitterness and astringency become stronger while green-related attributes become weaker as the brewing time and water temperature of green tea increases. This is also confirmed by the results of Miller et al [ 51 ], who found that heat treatment of 2 h at 80 and 90 °C reduced the green/grass flavors’ intensity to negligible levels.…”
Section: Discussionsupporting
confidence: 87%